MARKETING COMMUNICATION MIX AND COMPETITIVE ADVANTAGE: THE CASE OF RURAL BANKS IN GHANA - Tandoh, Isaac; Oppong-Mensah, Nicholas (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of this paper was to explore the relationship between two main variables.Marketing communications and competitive advantage. In addition, this research is conducted to test competitive advantage variables such as brand awareness, corporate image, brand position and customer awareness and loyalty and how influenced competitive advantage in the rural banking industry of Ghana.A multi-stage sampling technique was used in selecting the final 561 samples for the study. The study revealed that there is a significant relationship between marketing communications mix and competitive advantage as all the marketing communications elements positively and significantly influenced various variables of competitive advantage in this study. However, it was inferred from the results that, a single marketing communication tool was not enough to bring about a significant positive change in a competitive advantage variable of RCBs in the banking industry in Ghana. The study recommends that the management of the RCBs should adopt an integrated communications approach and embrace new marketing communications tools like social media and branding to create a sustainable competitive advantage.